2012
DOI: 10.1177/0145445512442214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peer-Mediated Implementation of Visual Scripts in Middle School

Abstract: Although research has investigated the impact of peer-mediated interventions and visual scripts on social and communication skills in children with autism spectrum disorders, no studies to date have investigated peer-mediated implementation of scripts. This study investigated the effects of peer-implemented scripts on a middle school student with autism, intellectual impairments, and speech-language impairment via a multiple baseline single-case research design across behaviors. The target student demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 34 publications
4
25
0
Order By: Relevance
“…The study findings are consistent with results obtained in other research that show PMI in and of itself may be essential but insufficient to improve social interactions between students with ASD and their peers (Ganz et al, 2012;Labbe-Poisson, 2009;McConnell, 2002;Sainato et al, 1992;Thiemann & Goldstein, 2004). In this research, including the current study, peer training did not significantly improve social initiations from the typically developing peers, and in turn it did not promote social interactions with the students with ASD.…”
Section: Research Focus Purpose and Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The study findings are consistent with results obtained in other research that show PMI in and of itself may be essential but insufficient to improve social interactions between students with ASD and their peers (Ganz et al, 2012;Labbe-Poisson, 2009;McConnell, 2002;Sainato et al, 1992;Thiemann & Goldstein, 2004). In this research, including the current study, peer training did not significantly improve social initiations from the typically developing peers, and in turn it did not promote social interactions with the students with ASD.…”
Section: Research Focus Purpose and Resultssupporting
confidence: 91%
“…However, when the researchers combined peer training with self-management, the treatment package did have positive effects on the social behaviors of the students. Similar findings were obtained in other studies in which PMI resulted in improvement in social skills for students with ASD when it was combined with other approaches such as self-management (Labbe-Poisson, 2009) and visual prompts (Ganz et al, 2012;Thiemann & Goldstein, 2004). The findings reported in these studies support the conclusion that peer training in and of itself might be necessary, but not sufficient, to facilitate social interactions among students with ASD and their peers (McConnell, 2002).…”
Section: Chapter One: Introductionsupporting
confidence: 88%
“…As the scripts were systematically faded, the stimuli on which the scripts were superimposed evoked the social interactions. Other script‐fading studies have demonstrated comparable results in teaching people with autism to interact with their peers (e.g., Ganz et al, ; Ganz, Kaylor, Bourgeois, & Hadden, ; Ledbetter‐Cho et al, ; Sarokoff, Taylor, & Poulson, ).…”
mentioning
confidence: 78%
“…For example, differential reinforcement of variability and lag reinforcement schedules, in which reinforcement is contingent upon the person displaying behavior that is novel or different from previous responses (Miller and Neuringer 2000;Lee et al 2007), have been used with persons with autism to increase diverse play behaviors and to decrease sameness behaviors such as time engaged in restricted behaviors and perseveration with objects (Boyd et al 2011). Also, there is a growing body of literature on the use of social scripts to increase social initiations, expand verbal repertoires, and ease participation into conversation (Ganz et al 2012;Lee and Sturmey 2014;Stevenson et al 2000). However, the authors were unable to find studies where social scripts were used specifically to facilitate transitioning from one topic to another.…”
Section: Discussionmentioning
confidence: 99%